SCREENING FOR SHEATH BLIGHT RESISTANT GENOTYPES AMONG MUTATED POPULATION OF RICE CV. PUSA BASMATI-1 - MEENA, SURESH CHAND; SINGH, VINEETA; ADHIPATHI. P; CHAND, RAMESH (The Bioscan, 2013)
The present investigation was undertaken to identify the resistant genotypes amongst mutated rice population of the variety Pusa Basmati-1 induced by the gamma radiation (15kr). The variability in disease reaction was observed among mutated rice genotypes. Out of the total 8345 mutant lines, 23 lines belong to same class depicting 0 to 20 AULPC value and 3052 mutant lines come under the class having more than 200 AULPC. Out of 8345 mutated rice population 298 resistant genotypes were identified after screening under field conditions. Significant variation was observed in the disease reaction among the selected mutant population with respect to control (nonmutated). The selected genotypes depicting very low AULPC (Area Under Lesion Progress Curve) value have been advanced to M2 generation and screened with non-significant deviation for disease score. Nonsignificant variation in morphological expression and in yield attributes among the selected mutants was also reported. Thus, these genotypes could be considered a potential source for disease resistance against the sheath blight of rice and could be used further in the crossing programme for development of sheath blight resistant rice variety.